2017
DOI: 10.1002/term.2533
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactors with hydrostatic pressures imitating physiological environments in intervertebral discs

Abstract: Intervertebral discs are normally exposed to a variety of loads and stresses but hydrostatic pressure (HP) could be the main biosignal for chondrogenic cell differentiation and maintenance of this tissue. Although there are simple approaches to intermittently expose cell cultures to HP in separate material testing devices, utilization of biomimetic bioreactors aiming to provide in vitro conditions mimicking those found in vivo, attracts special attention. However, design of such bioreactors is complex due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…There are still some contradictions in the prior studies about the effects of different pressure loading methods or intensities on the biological behavior of the IVD. The majority holds that the cells in NP and inner AF tissues mainly suffered hydrostatic pressure, because when a compressive force is applied to the IVD, the hydrostatic pressure within NP and inner AF is increased [9,27]. Hence, in the present study, we used the self-developed hydrostatic pressure bioreactor based on a pressure-transmitting mode achieved by a slight deformation of a flexible membrane in a completely sealed stainless steel chamber, to imitate in vivo microenvironment for NP and inner AF tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are still some contradictions in the prior studies about the effects of different pressure loading methods or intensities on the biological behavior of the IVD. The majority holds that the cells in NP and inner AF tissues mainly suffered hydrostatic pressure, because when a compressive force is applied to the IVD, the hydrostatic pressure within NP and inner AF is increased [9,27]. Hence, in the present study, we used the self-developed hydrostatic pressure bioreactor based on a pressure-transmitting mode achieved by a slight deformation of a flexible membrane in a completely sealed stainless steel chamber, to imitate in vivo microenvironment for NP and inner AF tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, the conclusions of the studies are not entirely consistent, due to the different quality of hydrostatic loading devices and observing methods used in the studies. It has been reported that the "physiological intensity (0.35-0.75 MPa)" of hydrostatic pressure acts as an anabolic factor for NP and AF cells, owing to the stimulation of proteoglycan synthesis [7][8][9]. In contrast, excessive pressure aggravates the catabolic metabolism of proteoglycan in NP and AF cells [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have emphasized the importance of bionic micromechanical characteristics (Wan et al, 2016). More specifically, biomaterials with natural NP and AF structures have been recommended for IVD reconstruction (Zvicer and Obradovic, 2018). Nevertheless, the complex modulus of the NP is 22 kPa (Bron et al, 2009), and the AF extra-fibrillar matrix modulus ranges from 10 to 50 kPa (Cortes et al, 2013), which is much greater than the modulus that favors IVD cell differentiation.…”
Section: Mechanical Characteristicsmentioning
confidence: 99%
“…Several methods exist to apply compressive stress to cells such as using a microfluidic platform 6,44 or a hydrostatic pressure system 45,46 . However, a system that exerts a constant contact compressive force is more suitable to simulate uncontrolled growth-induced mechanical compression found in solid tumor.…”
Section: Piezo1mentioning
confidence: 99%